Simulation Model of Muhammadiyah Food Product Buying Interest as a Sustainability Breakthrough - Fauziyah Nur Jamal; Gea Dwi Asmara; Bagus Gumelar; Mustika Rahmi; Ahmad Rizal Solihudin (Danadyaksa: Post Modern Economy Journal, 2026)
This study aims to determine the factors affecting the purchase interest of Muhammadiyah food products in Indonesia. SEM-PLS (Partial Least Squares–Structural Equation Modeling) software was used for data processing to further develop a simulation model of Muhammadiyah food product purchase interest. The hypothesis is that positive purchase interest will result in positive and stable green consumer behavior that can be seen in the next few years. The population of this study is all consumers in Indonesia. In this case, the sample used was 100 respondents. The results show that the developed simulation model can be a valuable reference for predicting stable purchase interest over the next few years. The implementation of this integrated strategy can increase consumer buying interest that not only buys products but also contributes to environmental sustainability and Islamic values. This model allows Muhammadiyah food product entrepreneurs to make the right decisions in effective marketing strategies that continue to provide value.